Auxin in Plant Defense Reactions: New Insights and Potential Applications for Resistance Breeding Programmes - Mainali, Ram Prasad; Nyaupane, Sushil (Journal of the Institute of Agriculture and Animal Science, 2023)
The role of auxin in growth and development in plants has been studied and documented since its discovery; however, its role in plant defense during pathogenic infection has been studied more recently. With the aim to provide new insights and update knowledge in this field of biology, this review was carried out focusing on the specific role of auxin and associated signaling against a wide array of bacterial and fungal pathogens, as special references. This review illustrates the role of auxin including indole-3-acetic acid, mechanism of auxin-responsive gene action, auxin signaling and associated crosstalk with other defense hormone pathways. Loads of evidence support that the biology of plants favoring repressed auxin signaling, auxin responsive defense gene activation and hormonal crosstalk with other associated defense hormones such as salicylic acid and jasmonic acid signaling pathway is vital for host defense against pathogens. As this paper unravels the role of auxin in plant defense, classical and molecular breeders would get new background insight into engineering plants with enhanced host plant resistance with the introduction of auxin responsive gene or manipulation of desirable auxin signaling or associated pathway. The current knowledge domain on plant defense during pathogen infection could be improved by considering multiple pathogens in nature, their interaction with other beneficial microbes and associated auxin manipulation in future research works.